Evaluation the power consumption on cutting parameters during CNC machining using taguchi method - Foo, Ming Wei (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Nowadays, the waste of energy (electrical) consumption in industries is increasing. This waste of energy consumption causes an effect on the environment. So to reduce the environment effects, the power consumption on industries need to be reduced. The objectives of this research are to investigate the effect of strength of material on the power consumption during turning process and to optimize the power consumption by controlling the cutting parameters during turning process by using Taguchi method.